Improvement Of Critical Thinking Ability For Elementary School V Class Students - Wahyuddin, Khaeruddin, Evi Ristiana (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
This study aims to measure the critical thinking skills of fifth grade elementary school students. This type of research is a quasi-experimental design with a pretest-posttest control group design. The population used in this study were all fifth grade students as a sample because it only consisted of 2 classes with a total of 25 people. The data obtained were analyzed using descriptive and inferential statistics. The results of the descriptive analysis obtained: (1) The average results of students' critical thinking skills in the experimental class before applying the problem-based learning model of 52.22 are in the very low category and 51.08 in the control class are in the very low category; (2) The average result of students' critical thinking skills in the experimental class after applying the problem-based learning model was 80.92 in the high category and 76.16 in the control class in the medium category; The results of the infrensial analysis state that (1) There is an effect of applying the problem-based learning model on critical thinking skills which is indicated by a sig value of less than 0.05, namely 0.00 0.05, which means rejecting Ho and accepting Ha; (2) There is an effect of applying the problem-based learning model on students' cognitive learning outcomes as indicated by a sig value of less than 0.05, i.e. 0.00 0.05, which means rejecting Ho and accepting Ha.